Slippery Surface Based on Photoelectric Responsive Nanoporous Composites with Optimal Wettability Region for Droplets' Multifunctional Manipulation. Issue 1 (20th November 2018) - Han, Keyu; Heng, Liping; Zhang, Yuqi; Liu, Yao; Jiang, Lei
Abstract: The development of responsive slippery surfaces is important because of the high demand for such materials in the fields of liquid manipulation on biochips, microfluidics, microreactions, and liquid‐harvesting devices. Although great progress has been achieved, the effect of substrate wettability on slippery surfaces stability is overlooked by scientists. In addition, current responsive slippery surfaces generally function utilizing single external stimuli just for imprecisely controlling liquid motion, while advanced intelligences are always expected to be integrated into one smart interface material for widespread multifunctional applications. Therefore, designing slippery surfaces that collaboratively respond to complex external stimuli and possess sophisticated composite function for expanding applications from controlling droplets motion to patterned writing is urgently needed but remains a challenge. Here, a photoelectric cooperative‐responsive slippery surface based on ZnO nanoporous composites is demonstrated. First, the effect of composite surface wettability on slippery surface stability is systematically researched and the optimum wettability region for fabricating stable slippery surfaces is determined. Furthermore, controllable droplet motion and patterned writing are realized on the same slippery surfaces under photoelectric cooperative stimuli, and the related response mechanism is also deeply studied. This kind of material has potential applications in biochips, microfluidics, in situ patterning, and water‐harvesting systems. Abstract : Photoelectric cooperative responsive slippery surfaces based on ZnO nanoporous composites are fabricated. The effect of surface wettability on slippery surface stability is systematically researched. Controllable droplet motion and patterned writing are realized by photoelectric cooperative stimuli on slippery surfaces, and the related response mechanism is deeply studied. This kind of material has potential applications in biochips, microfluidics, and in situ patterning.